2014
DOI: 10.4172/2329-9029.1000119
|View full text |Cite
|
Sign up to set email alerts
|

Plant Age Affects Wound-Induced Senescence in Lactuca Sativa L

Abstract: In the present study we investigated the performance of dark-stored wounded leaf discs and pieces (to some extent mimicking fresh-cut product) of Lactuca sativa L. in relation to the physiological maturity at harvest. We used two related genotypes, i.e. a green (cv. Troubadour) and a red butterhead (cv. Teodore) differing in their pigment levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Data used for calibrating and validating the lettuce models covered representative pigment ranges, contributing to successful PLSR modeling. The senescence of red and green lettuces in relation to the age of the plant at harvest was investigated in another work, with chlorophyll content varying approximately from 4.0 to 13.0 mg kg −1 . Also, lettuce chlorophyll content varying between 4.2 and 11.4 mg kg −1 were used when applying different N treatments in four common green leafy vegetables .…”
Section: Resultsmentioning
confidence: 99%
“…Data used for calibrating and validating the lettuce models covered representative pigment ranges, contributing to successful PLSR modeling. The senescence of red and green lettuces in relation to the age of the plant at harvest was investigated in another work, with chlorophyll content varying approximately from 4.0 to 13.0 mg kg −1 . Also, lettuce chlorophyll content varying between 4.2 and 11.4 mg kg −1 were used when applying different N treatments in four common green leafy vegetables .…”
Section: Resultsmentioning
confidence: 99%
“…In a study performed in our laboratory in parallel to the here reported one, Witkowska and Woltering (2013) found that younger leaves of both green and red butterhead lettuce expressed better capacity to cope with wound-induced browning and senescence than older leaves. However, there was not a clear relation between plant age and either the vitamin C or total antioxidant levels.…”
Section: Wound-induced H 2 O 2 Production In Excised Leaf Disks Is Agmentioning
confidence: 48%
“…Fresh‐cut butter head lettuce, of both green and red genotypes, prepared from younger plants (35 days of growth) had day‐shelf life extension (i.e. time to reach an unacceptable quality with slightly visible browning) compared to those from older plants (49 days of growth) . Previous studies also confirm the higher browning in fresh‐cut products as maturity advances, based on core and stem length.…”
Section: Impact Of Harvest Related Factors On the Quality Of Raw Matementioning
confidence: 72%